TINJAUAN ALUR PROSEDUR PELAYANAN PASIEN RAWAT JALAN PESERTA BPJS GUNA MENINGKATKAN KUALITAS PELAYANAN KESEHATAN DI RSUD BANDUNG KIWARI - Pujilestari, Intan; Monica, Rizqy Dimas; Ratiana, Widia (Jurnal TEDC; Vol 18 No 1 (2024): JURNAL TEDCDO - 10.70428/tedc.v18i1.785, 2024)
The increase in BPJS patients at Bandung Kiwari Hospital is something that needs to be considered in their services, the inhibiting factors are employees who still cannot correct computer system errors, officers still rely on IT employees to justify them, so the registration service process becomes hampered and late due to waiting for the team Different IT floors, apart from that there are still employees who are lacking in conveying information to patients. The purpose of this study was to find out how the flow of procedures for outpatient registration services for BPJS users in order to improve the quality of health services at Bandung Kiwari Hospital. The research method used is descriptive method with a qualitative approach with the subject, namely the registration officer, and the object, namely the BPJS registration flow. Data collection techniques are by interview, observation and documentation study. The research instrument uses stationery, stop watch, and interview guidelines. Based on the Hospital SPO for outpatient registration of BPJS participants, it is explained that employees must greet, but employees are still normal to receive patients, and officers are still not reliable enough to correct computer system errors, besides that hospitals are lacking in conveying information to patients so there are still patients lack information for BPJS registration which must register with predetermined conditions. The author suggests that the Hospital provide facilities that new patients can see regarding the requirements for registering to use BPJS and provide motivation to employees regarding empathy for patients.